Pengaturan Peraturan Daerah Kabupaten Solok Nomor 6 Tahun 2002 tentang Berpakaian Muslim dan Muslimah dalam Perspektif Hukum Ketatanegaraan Indonesia - Ari Wibowo (Jurnal Hukum IUS QUIA IUSTUM, 2007)
The issuance of various shariah based ordinances in many provinces and residences across the country, such as those which have been issued in Solok Residence, namely ordinance no. 6 of 2002 on Moslem Attire, may lead to the violence against the rights of the religion’s adherents to be protected by the state in serving religious tenets. If such kind ordinances let to be issued more, may lead to the disintegrate of the country.